DELINEASI NILAI KONDUKTIVITAS LISTRIK, TEKSTUR TANAH DAN METODE STATISTIK K-MEANS CLUSTER UNTUK PERKEBUNAN MELON DAN BUAH NAGA DI WILAYAH KALIMANTAN BARAT - Nelsa Indah Artamevia, - (2022)
Melon and dragon fruit are one of the plants that are cultivated on peat soil. The use of peat land as plantation land must be in accordance with the conditions for growing the plant itself. This study aims to determine the delineation based on the value of electrical conductivity, soil texture and supported by the K-Means Cluster statistical method on peat land in melon and dragon fruit plantations, Rasau Jaya Village, West Kalimantan. Electrical conductivity measurements were carried out using a conductivity meter, soil texture class was determined using the USDA (Unied States Department of Agriculture) classification method, clustering was carried out using the K-Means Cluster statistical method, and observations of soil physical characteristics were carried out by seeing, feeling and using the Munsell book. Soil Color Chart. The results showed that the melon plantation soil had 2 layers. Layer 1 is in the range of electrical conductivity values of 0.04 dS/m - 0.14 dS/m, has a clay texture and has a color code of 10 YR 2/1. Layer 2 is in the range of electrical conductivity values of 0.02 dS/m - 0.07 dS/m, has a sandy loam texture and has a soil color code of 10 YR 2/1. While the dragon fruit plantation has 3 layers of soil. Layer 1 is in the range of electrical conductivity values of 0.03 dS/m - 0.10 dS/m, has a sandy loam texture and has a color code of 5 YR 2.5/1. Layer 2 is in the range of electrical conductivity values of 0.05 dS/m - 0.30 dS/m, has a clayey texture and has a color code of 10 YR 2/2. Layer 3 is in the range of electrical conductivity values of 0.23 dS/m - 0.42 dS/m, has a clay texture and has a color code of 10 YR 2/1.